A conceptual model of depositors’ trust and loyalty on hajj institution - case of Lembaga Tabung Haji Malaysia - Abd Rahman, Nur Hasnida; Mohd Sofian, Fatimah Noor Rashidah; Abdullah Asuhaimi, Fadhilah; Shahari, Farihana (Econjournals, 2020)
Being established as a special Islamic financial institutions dedicated for managing hajj fund, Lembaga Tabung Haji (TH) plays a crucial role to ensure going concern of the institutions. Thus, it is highly important to preserve depositors trust and loyalty on the institution. Financial and management issues faced by TH, couple with the widespread use of social media reporting inaccurate information about the institutions may give impact to the depositors’ trust, evidencing by a sudden deposits withdrawal and closure of account in year 2017. As it is a special institution only for Muslims, its depositors carry different characteristics as compared to the other financial institutions. Using literature survey, this study develops a conceptual model to examine the depositors’ trust and loyalty on the institution by examining three mediating variables namely depositors’ financial literacy, depositors’ understanding about hajj and depositors’ awareness about current development of the institutions. Finally, both theoretical and practical implications were also discussed.